DIVERSITY OF SECONDARY METABOLIT OF ARTOCARPUS ALTILIS - Erwin - (PROSIDING SEMINAR KIMIA, 2015)
Artocarpus altilis (Synonyms: Artocarpus communis and Artocarpus incisus.) Is a fast growing plant and spread it evenly in tropical and sub-tropical forests. In many countries, this plant is known as a traditional medicine such as in Taiwan is used as a remedy swelling of the liver, is anti-inflammatory, and has a detoxifying effect (detoxifyng), while in Indonesia, the leaves is using as an external medicine and to treat swelling of lymph. From various reports the results showed A. altilis contain steroids, chalcone, stilbene, flavonone, flavanone, aurone, and quinonoxanthone. Among the compounds which are found potentially as a hypo-allergenic and anti-tumor drug, tyrosinase and α-glucosidase inhibitory activities, and cathepsin inhibition.